Controller Placement in Software Defined Networking - Habibabadi, Mohammad Ashrafi (2019)
This work focuses on the placement of controllers in software de ned networking architectures. The goal is to optimize the latency besides having reliability and scalability in mind. Two mathematical models are proposed, the former determines the optimal controller location in single mapping scenarios and the latter determines the optimal location in multiple mapping scenarios. A scalability factor is introduced to equally decrease load among controllers, increasing the load to capacity gap at controllers in any failure scenario. The results show that the model nds the optimal location while taking redundancy and scalability into consideration.